Strategic Monograph Publishing in the Humanities and Social Sciences in Australia. Issue 4 (2nd October 2021) - Mrva-Montoya, Agata
ABSTRACT: Drawing on the findings from semi-structured interviews with 21 academics in the humanities and social sciences (HSS) at Australian universities, this article explores how academic authors understand prestige in scholarly book publishing, and how the institutional pressures, and their personal and professional goals shape their publishing strategy. University presses in the Global North were regarded higher than global commercial publishers, which in turn were seen as more reputable than Australia-based university presses. The application of such HSS-wide hierarchies of publishers devoid of disciplinary nuance in performance assessments has been criticised as counterproductive and even harmful, with a detrimental impact on the scholar's autonomy and research agendas. Nevertheless, the need for academics to carefully choose the publisher is considered key in the current competitive institutional and publishing environment. The study develops a framework to guide academics' publishing strategy, which uses audience, quality and time as key elements that need to be taken into consideration when deciding where to publish their book-length work. The findings of the study will be useful to HSS academics who are interested in refining their book publishing strategy and staff in libraries and in research support roles who advise academics, especially early career researchers, on their publishing decisions.